Canons and factions in the cathedral of Valencia during the first half of the 16th century - Callado Estela, Emilio (Cuadernos de Historia Moderna, 2021)
The cathedral canons did not remain aloof from the factions that drew together a major part of the Valencian society during the modern age, particularly during the 16th century. The analysis of some relevant cases –for the family origin of those who star, their cursus honorum and the significance of the criminal episodes in which they were involved– would confirm the interweaving between the ecclesiastical world, represented by these clergy, and the described phenomenon of banditry, at least in the first half of this century.
Keywords: canons; cathedral; Valencia; banditry; 16th century